CULTURALLY RESPONSIVE TEACHING LEARNING MODEL FOR ELEMENTARY SCHOOLS IN PADANGSIDIMPUAN CITY - Nashran Azizan; Maulana Arafat Lubis; Muhammad Amin; Hamidah Hamidah; Latifa Annum Dalimunthe; Parulian Siregar (PD PGMI se Indonesia, 2026)
Developing students’ social character is a central goal of elementary education. This research aims to develop and validate a CRT model integrated with the local cultural values of poda na lima to strengthen students’ social character in PPKn. The research adopted the Plomp educational design research model, encompassing the stages of preliminary research, prototyping, and assessment. The participants were 106 fourth-grade students from a public elementary school in Padangsidimpuan. Data were collected through expert validation sheets, questionnaires, classroom observations, and learning outcome tests, and analyzed using descriptive statistical methods. The results indicate that the developed model achieved high levels of validity, practicality, and effectiveness in improving students’ social character. The integration of poda na lima values within the CRT framework provides a culturally grounded pedagogical strategy that aligns learning with students’ sociocultural backgrounds. The study also produced several supporting instructional materials, including a CRT model book, RPP, BG, BS, and LKS. This research contributes to the advancement of culturally responsive pedagogy by embedding indigenous cultural values into instructional design, offering an innovative approach to strengthening character education in elementary schools.